Getting Bullied in the Nonprofit Sector: The Dark Side of Public Service Motivation and Political Behavior - Geoff Plimmer; Alina Haider; Kamal Badar; Ao Zhou (Nonprofit and Voluntary Sector Quarterly, 2026)
Bullying is harmful and prominent in nonprofit organizations (NPOs), yet it remains understudied. This article investigates how public service motivation (PSM), which is trait-like, prosocial and vital to NPOs, may counterintuitively expose NPO workers to being bullied. Notwithstanding PSM’s many benefits, recent studies have identified a dark side of PSM that potentially may attract bullying from coworkers. This survey-based study in the New Zealand nonprofit sector ( N = 880) draws on social exchange theory and conservation of resources theory to examine the relationship between PSM and being bullied, the role of political behavior as a mediator, and constructive leadership as a moderator. Findings support all hypothesized relationships, except one. The article concludes with theoretical implications and practical recommendations to address challenges stemming from the dark side of PSM as well as to curb bullying in NPOs.